TEMEL DEMOGRAFİK ve SAĞLIK DÜZEYİ ÖLÇÜTLERİ AÇISINDAN TÜRKİYE İLE AVRUPA BİRLİĞİ’NE (AB) ÜYE ÜLKELERİN KARŞILAŞTIRILMASI - VEHİD, Suphi (Cerrahpaşa Medical Journal, 2019)
Background.- In recent 40 years, world population has been changed. Rate of developed countries population was decreased to one fifth from one third of the world population. Due to this change, differences between developed and developing countries are raised. During recent forty years, relation between Turkey and EU was the one of the top subject of public agenda, and at least Turkey were invited to be candidate member of the union by the 1999 Helsinki decisions. Design.- In this study, comparison between Turkey and member of European Union countries tried to be done according to some of their basic demographic and health indicators. Results.- Apart from differences on basic demographic situations, main differences were found on death rates such as maternal mortality, new born mortality and mortality of children under five years of age, which are very high in Turkey against to the members of EU countries. Conclusion.- These differences suggest that there is a thoughtful situation on the level and distribution of the primary health care services in Turkey against to the members of EU countries, although it is possible to think optimistic that these differences will become less by looking passed values.